2006
DOI: 10.2478/s11532-006-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

A new reagent system for the highly sensitive spectrophotometric determination of selenium

Abstract: Highly sensitive and simple spectrophotometric determination of selenium is described for the determination of selenium(IV) using a new reagent leuco malachite green. The method is based on the reaction of selenium(IV) with potassium iodide in an acidic condition to liberate iodine, the liberated iodine oxidizes leuco malachite green to malachite green dye. The green coloration was developed in an acetate buffer (pH 4.2–4.9) on heating in a water bath (∼ 40 °C). The formed dye exhibits an absorption maximum at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The sampled marron from each tank culture were killed to determine the total soluble Se in haemolymph, hepatopancreas and muscle tissues. Total soluble Se was determined using a spectrophotometric method according to Revanasiddappa and Dayananda (). Briefly, 4 mL concentrated HNO 3 was added to all samples and heated at 80°C for 1 h, then another 3 mL HNO 3 was added to the solution.…”
Section: Methodsmentioning
confidence: 99%
“…The sampled marron from each tank culture were killed to determine the total soluble Se in haemolymph, hepatopancreas and muscle tissues. Total soluble Se was determined using a spectrophotometric method according to Revanasiddappa and Dayananda (). Briefly, 4 mL concentrated HNO 3 was added to all samples and heated at 80°C for 1 h, then another 3 mL HNO 3 was added to the solution.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed method provides a limit of detection of the same order than that obtained by using NPDPTC after a previous separation of the gas phase generation, 9 and clearly lower than other photometric procedures. 3,7,8 It seems that kinetic spectrophotometric approaches provide an enhancement of the LOD and astonishing the sensitivity reported for FIA spectrophotometric determination with MBTH is one order of magnitude better than that obtained by us. However, on looking through the aforementioned study, 12 it can be seen that authors reported a sensitivity of 0.1875 for the concentration range between 0.050 and 0.500 mg L -1 which is clearly lower than the value of 0.501 obtained in this study for the range between 0.010 and 0.500 mg L -1 and thus it is surprising that they could found a LOD of 0.00025 mg L -1 nor for using a 2σ criterion.…”
Section: Effect Of Reagent Concentrationmentioning
confidence: 59%
“…1,2 In terms of sources of selenium in the environment it can be noticed volcanic eruption, insecticides, fertilizers, smelting ceramic, metallurgical operation, glass rubber accelerators, paints, dyes and electronic goods, 3 additionally there are some industrial and agricultural processes which can cause the presence of Se in natural waters, 4 According to the sanitary and hygiene standards, 0.05 mg L -1 is the maximum permissible concentration of Se in water, 5 and 0.1-0.2 mg dm -3 the Threshold Limit Value (TLV) for selenium compounds in air. 6 Spectrophotometric methods reported in the literature for the determination of Se in water are based on the batch reaction of Se with potassium iodide in an acidic medium to liberate iodine, which oxidizes leuco malachite green, 3 or Variamine Blue 7 to produce a coloured product; oxidation of p-nitroaniline by selenium (IV) followed by reaction with N-(1-naphthalene-1-yl)ethane-1,2-diamine dihydrochloride (NEDA) 8 or previous gas extraction of Se followed by reaction with and 2-(p-nitrophenyl)-3,5-diphenyltetrazolium chloride. 9 Kinetic spectrophotometric methods have been also reported based on the reduction of trisodium 4,5-dihidroxi-3-[(p-sulfophenyl)]-2,7-naphtalenedisulfonic acid by sulphide in Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover these methods have many individual limitations like use of sophisticated instruments, time consuming operation, requires multi-step procedures for pre-concentration of analyte and low selectivity with higher interference problems. In addition to the above-mentioned methods, studies on molecular spectroscopy-based articles show some drawbacks such as having low molecular absorption coefficients in the ultraviolet region, lack of any report about cationic interferences studies, and in some cases the reported detection limits are not competitive with the results of atomic spectroscopic techniques [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%